Menopausal problems and related health promotion behaviours among post-menopausal women - Cyriac, Salini Lisa; Viswanath, Lekha; Thurkkada, Anju Philip (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Menopause is a natural biological process that ends a woman’s reproductive years. The typical age range is 45 to 55 years old, with an average age of approximately 51. In addition to symptoms including mood swings, hot flashes, nocturnal sweats, dry vagina, and disrupted sleep, women can face a variety of issues, including irregular menstrual periods. The purpose of the study was to identify the menopause-related health promotion behaviours among post-menopausal women. Methods: Descriptive survey design was used for this study. One-stage cluster probability sampling was used for the selection of 108 post-menopausal women. After getting consent from the participants data was collected through an interview schedule and a health promotion behaviour assessment tool. The Institutional Ethics Committee granted ethical clearance before the study began. Before data was collected, each participant gave their written informed consent. Results: Out of 108 participants, 51.8% of them followed good dietary habits, 26.8% engaged in exercises daily and those who practiced stress reduction measures like yoga, and meditation were 23.1%. Conclusions: The study results show that menopausal women are unaware of the health promotion behaviours that should be adopted in managing menopausal problems. This provides evidence for giving importance to menopausal problems and related health promotion behaviours.